2004
DOI: 10.1161/01.hyp.0000141411.94596.0f
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Pressure Lowering Effect of Chronic Atenolol Therapy in Hypertension and Vasoconstrictor Sympathetic Drive

Abstract: Abstract-Although the ␤ 1 -adrenergic blocking agent atenolol is an established antihypertensive therapy, its effect on peripheral sympathetic vasoconstrictor drive has remained controversial. In patients with hypertension, atenolol therapy has been reported to either increase or have no effect on peripheral vascular resistance, despite other reports showing no change or a decrease in peripheral sympathetic drive. This study was designed, in patients with untreated essential hypertension (EHT), to quantify cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…Although we cannot entirely exclude some influence of these agents, it is known in hypertensive patients that chronic ACE inhibitor therapy does not affect MSNA levels, 22 ARBs may decrease it, 23 and ␤-blockers may have no effect or decrease MSNA. 24,25 In obese hypertensive subjects, chronic hydrochlorothiazide therapy that lowers arterial pressure did not significantly affect MSNA levels. 23 We did not stop antihypertensive therapy in order to obtain comparable arterial pressure levels.…”
Section: Discussionmentioning
confidence: 95%
“…Although we cannot entirely exclude some influence of these agents, it is known in hypertensive patients that chronic ACE inhibitor therapy does not affect MSNA levels, 22 ARBs may decrease it, 23 and ␤-blockers may have no effect or decrease MSNA. 24,25 In obese hypertensive subjects, chronic hydrochlorothiazide therapy that lowers arterial pressure did not significantly affect MSNA levels. 23 We did not stop antihypertensive therapy in order to obtain comparable arterial pressure levels.…”
Section: Discussionmentioning
confidence: 95%
“…45 On the other hand, in studies in subjects with hypertension, therapy with the b-blockers bisoprolol and atenolol did not influence the sympathetic drive measured with MSNA. 46,47 Furthermore, studies with regard to calcium channel blockers showed that chronic therapy did not change MSNA. 48 In our study, patients had been taking antihypertensive drugs for at least 3 months before the study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that nebivolol vasodilates the human forearm vasculature through the L-arginine pathway, 14 improves small artery distensibility index, and increases endothelium-dependent cutaneous vasodilation. 15 At the same time, cardioselective BB do not reduce total peripheral resistance or sympathetic activity, 16 which may lead to small artery vasoconstriction and increased media:lumen ratio. 17 The AIx and pulse pressure amplification are related to wave reflection depending on the amplitude and site of wave reflection and on the speed at which pressure waves travel along the arterial tree.…”
Section: Bb and Reduction In Central Aortic Pressurementioning
confidence: 99%